ANALISIS NILAI KARAKTER PADA BUKU SISWA TEMATIK MUATAN IPS KELAS IV SEKOLAH DASAR - Nur Arrifa, Salma; Maria Zulfiati, Heri (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study aims to describe the educational values characters contained in the fourth-grade student's theme book 1 â€œThe Beautiful of Togethernessâ€ curriculum 2013, especially social studies subjects. This research is descriptive qualitative research. The data in this study are statements that contain and show the value of character education. Data was collected using reading, noted, and document analysis. Data validity used triangulation of source and triangulation of methods. Of the 18 values of the characters education launched by the Ministry of National Education, found 7 values of character education are available in the This study aim was to describe the educational values characters contained in the fourth-grade student's theme book 1 â€œThe Beautiful of Togethernessâ€ curriculum 2013, especially social studies subjects namely (1) religious, (2) tolerance, (3) democratic, (4) patriotism, (5) curiosity, (6) love peace, (7) like reading. These educational values characters are conveyed through story text, quotes, and assignments.